NUMERICAL METHODS FOR SOLUTION OF LINEAR AND NONLINEAR PROBLEMS OF POLYMER GELS MECHANICS - Denisyuk, E.Ya. (Perm Federal Research Centre Journal, 2016)
Boundary problems, describing the stress-strained state of statically loaded polymer gels under mechanical and thermodynamic equilibrium, are formulated. Their variational formulation is given. Their finite element approximation is implemented based on the mixed finite element method. The implementation of the proposed algorithms is carried out. The effects and phenomena, occurring in polymer gels under deformation in a solvent, are examined by numerical simulation.